ANALYSIS OF WORK MOTIVATION AND WORK DISCIPLINE OF EMPLOYEE AT WIYUNG SEJAHTERA HOSPITAL SURABAYA - Natasya Salsabilla; Popy Puspitasari; Dani Nasirul Haqi; Ainur Rofiq; Ratna Dwi Wulandari (The Indonesian Journal of Public Health, 2022)
Introduction: Work discipline is the obedient attitude of an employee towards the rules that apply in the workplace. Work discipline directly affects work productivity. Methods: This study aimed to investigate the correlation of work motivation and work discipline of the employee at Wiyung Sejahtera Hospital Surabaya. This study was an observational analytical research with cross sectional method, where each of the respondents was observed or interviewed for once. The samples used proportional random sampling with a sample size of 80 respondents who were hospital employees. Independent variable in this study was work motivation and a dependent variable was dicipline of employee. Data were analyzed by using spearman. Result: The respondents’ characteristics were mostly female (81.25%) with age criteria age 21-30 years old (80.0%). Meanwhile, the characterictic based on educational level suggested that more than half of respondents were diploma graduates(67.5%)  and have the most work periode for more than 3 years (33.75%). The majority of respondents had a moderate level of work motivation at 41.3% and the majority of respondents had a moderate level of work discipline at 42.5%. The results showed that there was correlation between work motivation and work discipline (p = 0.000). Conclusion: It can be concluded that there is a relationship between work motivation and work discipline of employee at Wiyung Sejahtera Hospital Surabaya. As the relation is very strong, an employee who has a high level of work motivation will have a high level of work discipline too and otherwise.  Keywords: work motivation, work discipline,Wiyung Sejahtera Hospital